Financial literacy amongst Portuguese students attending higher education on business related courses - Sebastião, Rui Pedro Assureira Ferreira Silva (2019)
Financial markets are global and financial products that are increasingly complex. Therefore, an individual’s financial knowledge is vital for informed decision-making enabling the best personal financial management possible. Given the importance of financial literacy in people’s lives, its determinants have tried to be identified to understand how it influences financial literacy levels, namely among young people. Hence, the goal of this study will be to assess the level of financial literacy of young Portuguese students, addressing the impact of the level of education on the financial literacy of college students. To test this, data from a questionnaire distributed to both Bachelor’s and Master’s students in business related courses at higher education institutions (namely Coimbra Business School and the Economics Faculty of Coimbra University) and through social media (namely Facebook) were analysed. The main findings were that both the level of the degree being studied (whether either a bachelor’s or master’s degree is being studied) and the academic background of the individual’s parents have a positive impact on financial literacy. Furthermore, the level of financial literacy of Portuguese students attending higher education is low, especially in terms of their knowledge of the main financial concepts.